The transcription factors DcHB30 and DcWRKY75 antagonistically regulate ethylene-induced petal senescence in carnation (Dianthus caryophyllus). (15th September 2022) - Xu, Han; Wang, Siqi; Larkin, Robert M; Zhang, Fan
Abstract: Although numerous transcription factors with antagonistic activities have been shown to contribute to growth and development, whether and how they regulate senescence in plants is largely unknown. In this study, we investigated the role of antagonistic transcription factors in petal senescence in carnation ( Dianthus caryophyllus ), one of the most common types of ethylene-sensitive cut flowers produced worldwide. We identified DcHB30 that encodes a ZF-HD transcription factor that is down-regulated in ethylene-treated petal transcriptomes. We found that silencing DcHB30 accelerated ethylene-induced petal senescence and that DcHB30 physically interacts with DcWRKY75, a positive regulator of ethylene-induced petal senescence. Phenotypic characterization and molecular evidence indicated that DcHB30 and DcWRKY75 competitively regulate the expression of their co-targeted genes DcACS1, DcACO1, DcSAG12, and DcSAG29 by reciprocally inhibiting the DNA-binding activity of each other on the gene promoters. This transcriptional regulation mechanism demonstrates that these transcription factors serve as positive and negative regulators in ethylene-induced petal senescence in carnation. Thus, our study provides insights into how antagonizing transcription factors regulate plant senescence. Abstract : The transcription factors DcHB30 and DcWRKY75 competitively regulate expression of their co-targeted genes, thereby integrating ethylene signaling and regulating petal senescence in carnation.